Intonation of declarative, imperative and interrogative sentences in the perception of adult female users of Polish - Wysocka, Marta (Papers in Linguistics, 2024)
The article is concerned with categorical perception of sentence intonation. Its theoretical part presents conclusions from the literature on the semantics of voice pitch changes and sentence intonation, with particular reference to the Polish language. The empirical part presents the methodology and results of the author’s own research on the perception of intonation of isolated declarative, imperative and interrogative sentences. The obtained results lead to the conclusion that the most important factor for assigning individual utterances to specific sentence categories is the general direction of the pitch of voice in the final segment of the utterance. It allowed the respondents to identify interrogative sentences, which were recognized with the greatest correctness. Declarative and imperative sentences, characterized by the falling final intonation, were less often correctly identified, yet these two categories differed in other features: the exact course of pitch changes in the final syllables, vowel length and distribution of intensities and (within them) their temporal characteristics, average values of fundamental frequency, intensity and duration of whole utterances, and ranges of their intonation contours. This leads to the conclusion that these characteristics did not play a significant role in the categorical perception of sentence intonation exemplified in the presented study.